Characterization of Tigecycline Resistance Among Tigecycline Non-susceptible Klebsiella pneumoniae Isolates From Humans, Food-Producing Animals, and in vitro Selection Assay - Moghimi, Mohaddeseh; Haeili, Mehri; Mohajjel Shoja, Hanieh (Frontiers in Microbiology, 2021)
Emergence of extensively drug-resistant isolates of Klebsiella pneumoniae has prompted increased reliance on the last-resort antibiotics such as tigecycline (TGC) for treating infections caused by these pathogens. Consumption of human antibiotics in the food production industry has been found to contribute to the current antibiotic resistance crisis. In the current study, we aimed to investigate the mechanisms of TGC resistance among 18 TGC-non-susceptible (resistant or intermediate) K. pneumoniae (TGC-NSKP) isolates obtained from human (n = 5), food animals (n = 7), and in vitro selection experiment (n = 6). Isolates were genotyped by multilocus sequence typing (MLST). ramR, acrR, rpsJ, tetA, and mgrB (for colistin resistance) genes were sequenced. The presence of tetX, tetX1, and carbapenemase genes was examined by PCR. Susceptibility to different classes of antibiotics was evaluated by disc diffusion and broth macrodilution methods. The expression level of acrB was quantified by RT-qPCR assay. The 12 TGC-NSKP isolates [minimum inhibitory concentrations (MICs) = 4–32 mg/l] belonged to 10 distinct sequence types including ST37 (n = 2), ST11, ST15, ST45, ST1326 (animal isolates); ST147 (n = 2, human and animal isolates); and ST16, ST377, ST893, and ST2935 (human isolates). Co-resistance to TGC and colistin was identified among 57 and 40% of animal and human isolates, respectively. All human TGC-NSKP isolates carried carbapenemase genes (blaOXA–48, blaNDM–1, and blaNDM–5). tetX/X1 genes were not detected in any isolates. About 83% of TGC-NSKP isolates (n = 15) carried ramR and/or acrR alterations including missense/nonsense mutations (A19V, L44Q, I141T, G180D, A28T, R114L, T119S, Y59stop, and Q122stop), insertions (positions +205 and +343), or deletions (position +205) for ramR, and R90G substitution or frameshift mutations for acrR. In one isolate ramR amplicon was not detected using all primers used in this study. Among seven colistin-resistant isolates, five harbored inactivated/mutated MgrB due to premature termination by nonsense mutations, insertion of IS elements, and frameshift mutations. All isolates revealed wild-type RpsJ and TetA (if present). Increased expression of acrB gene was detected among all resistant isolates, with the in vitro selected mutants showing the highest values. A combination of RamR and AcrR alterations was involved in TGC non-susceptibility in the majority of studied isolates.